Combination Chemotherapy in Advanced Adrenocortical Carcinoma - Fassnacht, Martin; Terzolo, Massimo; Allolio, Bruno; Baudin, Eric; Haak, Harm; Berruti, Alfredo; Welin, Staffan; Schade-Brittinger, Carmen; Lacroix, André; Jarzab, Barbara; Sorbye, Halfdan; Torpy, David J; et al. (The New England journal of medicine, 2012)
In this large international study of patients with adrenal cancer, a rare, treatment-refractory disease, mitotane plus a combination of etoposide, cisplatin, and doxorubicin had greater antitumor activity than mitotane plus streptozotocin. Adrenocortical carcinoma is a rare cancer (estimated incidence, 0.7 to 2.0 cases per 1 million population per year) 1 , 2 with a poor prognosis; the 5-year survival rate is less than 15% among patients with metastatic disease. 3 – 7 Mitotane is the only drug approved for the treatment of adrenocortical carcinoma and is used both as adjuvant therapy and for advanced disease, 8 – 14 although its efficacy has never been shown in a randomized trial. The experience with other antineoplastic drugs for the treatment of this disease is even more limited. Current treatment strategies for advanced disease are based exclusively on retrospective series . . .